(untitled) (Vox Batauli, 2024)
This paper examines the treatment of gender and class roles in the Nepali cultural film Deuki, which highlights the contemporary practices and rituals prevalent in Far-Western Province of Nepal. The primary objective is to analyze the performance of superstitious beliefs and practices associated with the ’Deuki’[1] system, focusing on the injustices faced by girls who are auctioned under the guise of ’Deuki Pratha[2].’ This research reveals that these girls experience severe oppression and mistreatment, often being denied agency and basic rights. However, it posits that through empowerment, even the most marginalized individuals can resist such injustices. The study employs theoretical frameworks from performance studies and feminist theory to explore these issues. The findings underscore a critical need for continued discourse on the socio-cultural implications of the ‘Deuki’ system, emphasizing that while awareness and advocacy have led to some decline in this practice, significant challenges remain. The conclusion advocates for further research and policy recommendations to address the evil cultural and ritual practices in Nepal.